On-Farm Hormonal Oestrus Synchronization and Mass Insemination Technique of Dairy Cattle in Sidama, Ethiopia (Global Journal of Science Frontier Research, 2021)
This study aimed to evaluate the efficiency of oestrus synchronization and mass insemination under the action research and development intervention. For the evaluation, a total of 126 and 883 dairy cattle were taken under action research and development intervention, respectively. The result of estrus response (90%) in action research was somewhat higher than the result obtained from development intervention (87.2%). The number of AI services per conception in action research was (1.75) lower than the development interventions (2.36). The result of conception was higher (58.4%) under action research than the development intervention (42.2%). The result further revealed that both in action research and development intervention conception significantly (P
Keywords: action research; synchronization; ai; dairy cattle; conception rate; sidama